Macroeconomic Conditions and Issuer Characteristics Shaping Corporate Sukuk Yield Spreads in Indonesia - Rifaldi Nurul Akbar; M. Abdurrozaq; Prama Siddiq Ramildan (Jambi Tuah Tengganai, 2026)
The Indonesian corporate sukuk market has expanded substantially over the past five years, yet investors and issuers face persistent uncertainty about which factors most strongly shape sukuk pricing. This study examines how macroeconomic conditions and issuer-specific characteristics jointly determine corporate sukuk yield spreads in Indonesia's sharia capital market. The analysis uses an unbalanced monthly panel of 87 corporate sukuk series issued by 42 firms listed on the Indonesia Stock Exchange between January 2020 and December 2025, yielding 4,176 series-month observations (mean T = 48 months; range 24–72 months). A two-step system Generalized Method of Moments (GMM) estimator was applied to address endogeneity, with macroeconomic variables (headline inflation, the BI 7-Day Reverse Repo / BI-Rate, the IDR/USD exchange rate, and the Jakarta Islamic Index return) and issuer characteristics (firm size, leverage, profitability, sukuk rating, and tenor) as explanatory variables. Diagnostic tests confirmed instrument validity (Hansen J-test p = 0.382) and the absence of second-order autocorrelation (AR(2) p = 0.214). Estimation results indicate that inflation and rupiah depreciation (the year-on-year percentage change in the log of the IDR/USD spot rate) raise yield spreads by 18.4 and 11.7 basis points, respectively, per one-percentage-point shock. In comparison, a one-notch rating upgrade compresses spreads by 27.3 basis points. Leverage exerts a positive and statistically significant effect on yield spreads (β = 0.142 on the proportion scale; a one-standard-deviation increase in leverage, equivalent to 0.18, widens spreads by about 2.6 basis points), whereas firm size and profitability reduce yield spreads. Sectoral heterogeneity reveals that financial-sector issuers respond more strongly to monetary shocks than non-financial issuers. The findings indicate that yield-spread dynamics in Indonesia's sharia capital market are shaped jointly by external macroeconomic shocks and internal issuer fundamentals, with rating quality functioning as the dominant compression mechanism. The results offer practical guidance for issuers structuring sukuk and for regulators calibrating disclosure requirements.